Beyond biophobia: positive appraisal of bats among German residents during the COVID-19 pandemic - with consequences for conservation intentions - Straka, TM; Coleman, JL; Macdonald, EA; Rogge, S; Kingston, T; Jacobs, MH (Springer, 2024)
Bats are often considered to be objects of biophobia, i.e., the tendency to respond with a negative emotion, such as fear or disgust, especially during the COVID-19 pandemic. However, existing studies have rarely compared both positive and negative emotions towards bats, leading to a potential negativity bias. This is crucial given the importance of emotions to bat-related human behaviours, such as in bat conservation-related actions. Via two online surveys conducted among German residents, we aimed to (i) assess positive and negative emotions towards bats, (ii) examine emotional shifts during the pandemic and (iii) explore how emotions, along with socio-demographics, predict the intent to perform bat-conservation actions. The first survey was undertaken ten months after the official declaration of the COVID-19 pandemic (December 2020 - January 2021), when bats gained societal attention due to speculation about the origin of the SARS-CoV-2 virus, and the second one ran twelve months later (January 2022). Overall, respondents held higher positive emotions than negative ones towards bats in both surveys, with no significant emotional shift observed. Positive emotions positively correlated with intentions to perform bat-conservation actions, while negative emotions showed no such relationship. Although our findings might be context-specific to populations in Germany or Europe, given European-Union legislation protecting bats and their habitats, they highlight the nuanced and complicated emotions that can be associated with certain species. Understanding these emotions can guide targeted conservation strategies and public outreach. Our results caution against overly generalising discussions of biophobia in conservation.